The Hog1 MAP Kinase Promotes the Recovery from Cell Cycle Arrest Induced by Hydrogen Peroxide in Candida albicans - Correia, Inês; Alonso-Monge, Rebeca; Pla, Jesús (Frontiers in Microbiology, 2017)
Eukaryotic cell cycle progression in response to environmental conditions is controlled via specific checkpoints. Signal transduction pathways mediated by MAPKs play a crucial role in sensing stresses, and in particular the cell integrity and HOG pathways whose canonical MAPK are activated in response to oxidative stress. In this work, we have analyzed the effect of oxidative stress induced by hydrogen peroxide in cell cycle progression in Candida albicans. Hydrogen peroxide was shown to induce a transient cell cycle arrest at the G1 phase of the cell cycle although phosphorylation of Mkc1 and Hog1 MAPKs can take place at all stages of the cell cycle. Interestingly, hog1 (but not mkc1) mutants required a longer time compared to wild type cells to resume growth after this challenge. Using GFP-labelled cells and mixed cultures of wild type and hog1 cells we were also able to show that hog1 mutants progress faster in the cell cycle under standard growth conditions (YPD at 37ºC), thus exhibiting a smaller cell size. This altered cell cycle correlates with an altered expression of the G1 cyclins Cln3 and Pcl2 in hog1 cells compared to the wild type strain. In addition, Hgc1 (a hypha-specific G1 cyclin) and Cln3 displayed a different kinetics of expression in the presence of hydrogen peroxide, indicating that Hog1 regulates the expression of G1 cyclins not only in response to oxidative stress but also under standard growth conditions. Hydrogen peroxide treated cells did not show Sol1 mRNA fluctuations present in untreated cells during cell cycle progression. In addition, it prevented degradation of Sol1, an effect which was enhanced in hog1 mutants. Therefore, in C. albicans, the MAPK Hog1 mediates cell cycle progression in response to oxidative stress arrest and participates in the cell size checkpoint during vegetative growth.